Activated human B cells induce inflammatory fibroblasts with cartilage-destructive properties and become functionally suppressed in return. Issue 5 (18th May 2015) - Störch, Hannah; Zimmermann, Birgit; Resch, Bastian; Tykocinski, Lars-Oliver; Moradi, Babak; Horn, Patrick; Kaya, Ziya; Blank, Norbert; Rehart, Stefan; Thomsen, Marc; Lorenz, Hanns-Martin; Neumann, Elena; et al.
Abstract : Background: Cross-talk between synovial fibroblasts (SF) and immune cells is suggested to play a crucial role in inflammation and chronification of rheumatoid arthritis (RA). The contribution of B cells in this process is poorly defined. Methods: Here, primary B cells from healthy donors were polyclonally activated and cocultured with SF of non-synovitic origin from patients with osteoarthritis. Results: In B–SF cocultures the concentrations of interleukin 6 (IL-6) and IL-8 increased manifold compared with single cultures even under physical separation and remained stable for several days after B-cell removal. Intracellular staining confirmed SF as key producers of IL-6 and IL-8, and B cells as main producers of tumour necrosis factor alpha (TNFα) and IL-1ß. Blocking experiments with a combination of anti-TNFα-antibodies and rIL-1RA significantly reduced SF cytokine production by up to 90%, suggesting that B-cell-derived TNFα and IL-1ß were crucial mediators of SF activation. Interestingly, B-cell cytokine production, CD25 expression and proliferation decreased in cocultures by at least 50%, demonstrating a negative regulatory loop towards the activated B cells. Inhibition of activin receptor-like kinase 5, a crucial component of the tumour growth factor ß (TGFß) signalling pathway, partly restored B-cell proliferation, suggesting a contribution of SF-derived TGFß in B-cell suppression. Besides cytokines, B-cell-activated SF also upregulated secretion of matrix metalloproteases such as MMP-3, thereby acquiring potential tissue destructive properties. This was confirmed by their invasion into human cartilage in the severe combined immunodeficiency mouse fibroblast invasion model in vivo. Conclusions: Interaction with activated B cells leads to conversion of non-arthritic SF into SF with a proinflammatory and aggressive RA-like phenotype, thereby suggesting a new, so far unrecognised role for B cells in RA pathogenesis.